2014
DOI: 10.1111/exd.12377
|View full text |Cite
|
Sign up to set email alerts
|

Topical E6005, a novel phosphodiesterase 4 inhibitor, attenuates spontaneous itch‐related responses in mice with chronic atopy‐like dermatitis

Abstract: proliferation and an enhancement of stimuli responses. Metabolic process genes are highly enriched in both hyper-and hypomethylated groups indicates that the shifting of metabolic processes might be important in skin ageing and may represent a fruitful area for further inquiry.We also observed a locus of a keratin gene cluster is hypermethylated in ageing skin, and this has been partially cross-validated by a human counterpart study that both Krt1 and Krt16 are hypermethylated in skin ageing (20). However, omi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…E6005 is a PDE4 inhibitor developed as a topical agent for AD. We and other group have demonstrated that topical application of E6005 immediately inhibits itching behaviour as well as itch-related cutaneous nerve firing in a mouse model (4,5). This effect was not due to a local anaesthetic effect ( Figure S1).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…E6005 is a PDE4 inhibitor developed as a topical agent for AD. We and other group have demonstrated that topical application of E6005 immediately inhibits itching behaviour as well as itch-related cutaneous nerve firing in a mouse model (4,5). This effect was not due to a local anaesthetic effect ( Figure S1).…”
Section: Introductionmentioning
confidence: 63%
“…Abstract: E6005, a potent, selective phosphodiesterase (PDE) 4 inhibitor, has been developed as a novel topical agent of atopic dermatitis (AD). It has been shown to inhibit itching in patients with AD as well in mouse models.…”
mentioning
confidence: 99%
“…31) On the other hand, a single topical application of E6005, a phosphodiesterase 4 inhibitor, decreases both spontaneous scratching and the activity of the cutaneous nerves, suggesting that E6005 inhibits itching by acting primarily in the periphery. 52,53) In ICR mice, acute cutaneous allergy increased hind-paw scratching and cutaneous nerve activity, the time courses of which were similar. 54) Terfenadine, a non-sedative H 1 histamine receptor antagonist, 55) inhibited neither the increased scratching nor nerve activity.…”
Section: Pruriceptive Activity Of Primary Sensory Nervesmentioning
confidence: 87%
“…The molecule has demonstrated selective and effective inhibition of PDE4 and prevents the elaboration of proinflammatory cytokines and adhesion molecules in both lymphocytes and monocytes [138]. E6005 has also demonstrated inhibition of hapten-induced scratching in sensitized mice and spontaneous scratching in mice with chronic dermatitis [138][139][140]. Preliminary studies of 76 subjects in Japan have established safety and tolerability in healthy volunteers as well as patients with AD [140].…”
Section: E6005mentioning
confidence: 99%